Determination of the aerodynamic characteristics of a wind power plant with a vertical axis of rotation - Tanasheva, Nazgul; Tleubergenova, Akmaral; Dyusembaeva, Ainura; Satybaldin, Amangeldy; Mussenova, Elmira; Bakhtybekova, Asem; Shuyushbayeva, Nurgul; Kyzdarbekova, Sholpan; Suleimenova, Saniya; Tussypbayeva, Ardak (Eastern-European Journal of Enterprise Technologies, 2023)
Wind energy is a commercially proven and rapidly developing type of electricity generation. Wind power plants with a vertical axis are more attractive and better suited for use in cities and urban environments where wind flow is less predictable compared to widespread wind power plants with a horizontal axis of rotation. This makes them a much better choice for both ground installation and/or for mounting on buildings and roofs that would otherwise limit the installation of higher horizontal turbine structures. The paper describes an experimental study of the drag force and its coefficient for wind turbines with a vertical axis of rotation. The object of the study is a laboratory model of a wind turbine with blades made in the form of rotating cylinders with a fixed blade. Experimental studies were carried out in the T-1-M wind tunnel, measurements of aerodynamic force were carried out using three-component scales. A distinctive feature of the work is the combined use of the lifting force of the cylinders, as well as the lifting force of the fixed plate. Due to this solution, when comparing with existing wind turbines with a vertical axis of rotation, it was found that the wind turbine in question prevails by 25‒100 % in the number of revolutions. The dependences of the drag force on the flow velocity and the drag coefficient on the Reynolds number from 1·104 to 4·104 are obtained. An uncertainty analysis was also carried out in order to determine the uncertainty by type A, B and the total uncertainty, from which it was found that the measurement error was 1.13 %. The field of the practical application of the results obtained in laboratory studies will be useful in the development of prototypes of wind turbines with a vertical axis of rotation